Analisis Problematika Pendidikan Islam Di Indonesia Abad 21 - Khozin, Ahmad (Journal of Islamic Education Policy, 2018)
Abstract., Indonesia is a country that is conducting educational development as mandated by the 1945 Constitution. In the course of the Law of the Republic of Indonesia Number 20 of 2003 on National Education System defines education as a conscious and planned effort to create an atmosphere of learning and learning process so that learners actively developing his potential to have spiritual spiritual strength, self-control, personality, intelligence, noble character, as well as the skills he needs, society, nation and state. In response, Islamic Education needs to get serious attention, especially among the intellectuals and thinkers of Islamic education in Indonesia. Various efforts are needed to restore Islamic education to its glory. To restore Islamic education to the glory, certainly not as easy as putting water on a cauldron. But there needs to be seriousness in reaching these ideals, including the seriousness in management and leadership of a reliable Islamic education institutions. In this paper the author will try to focus the discussion on the problems of Islamic education of the 21st century as well as solutions that can be offered in response to the problems of Islamic educationKeywords: Problematic Education, Islamic Education.                Abstrak., Indonesia merupakan negara  yang sedang melakukan pembangunan pendidikan sebagaimana yang diamanatkan Undang-Undang Dasar 1945.  Dalam perjalanannya Undang-Undang Republik Indonesia Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional mendefinisikan pendidikan sebagai usaha sadar dan terencana untuk mewujudkan suasana belajar dan proses pembelajaran agar peserta didik secara aktif mengembangkan potensi dirinya untuk memiliki kekuatan spiritual keagamaan, pengendalian diri, kepribadian, kecerdasan, akhlak mulia, serta keterampilan yang diperlukan dirinya, masyarakat, bangsa dan negara. Menyikapi hal tersebut, Pendidikan Islam perlu mendapat perhatian yang serius, terutama kalangan cendekiawan dan pemikir pendidikan Islam di Indonesia. Diperlukan ragam upaya untuk mengembalikan pendidikan Islam kepada kejayaannya. Untuk mengembalikan pendidikan Islam kepada kejayaan tersebut, tentu tidak semudah menaruh air di atas kuali. Namun perlu ada keseriusan dalam menggapai cita-cita tersebut, diantaranya keseriusan dalam manajemen dan kepemimpinan lembaga pendidikan Islam yang handal. Dalam makalah ini penulis akan mencoba memfokuskan pembahasan pada problematika pendidikan Islam abad 21 serta solusi-solusi yang dapat ditawarkan dalam menanggapi problematika pendidikan Islam tersebutKata Kunci:Problematika Pendidikan, Pendidikan Islam.